Droplets spectrum of air-assisted boom sprayers under different environmental and operational conditions - Sasaki, Robson S.; Teixeira, Mauri M.; Fernandes, Haroldo C.; Zolnier, Sérgio; Maciel, Christiam F. S.; Alvarenga, Cleyton B. de (Revista Brasileira de Engenharia Agrícola e Ambiental, 2016)
During pesticide spraying, the psychrometric conditions of the air may cause evaporation of the droplets along their trajectory from the nozzle to the target. Thus, this study aimed to evaluate the effect of air psychrometric conditions and operating pressure on the droplet spectrum of air-assisted boom sprayers. The test was performed using a prototype equipped with an axial fan, a flow homogenizer, temperature and relative air humidity sensors, a spray nozzle and a gas-heating system to warm up the airflow. With the assembled system and the aid of a particle analyser, the JSF 11002 spray nozzle was evaluated with respect to droplet spectrum in four air psychrometric conditions (7, 14, 21 and 28 hPa) and at four operating pressures (200, 300, 400 and 500 kPa). At the end, evaporation losses were observed during the sprayings. For a given operating pressure and for each increment of 1 hPa in vapor pressure deficit, there was a diameter reduction of approximately 0.0759, 0.518 and 1.514 μm for the parameters DV0.1, DV0.5 and DV0.9, respectively. The diameter of the droplets decreased as the operating pressure increased.

Durante a aplicação de agrotóxicos as condições psicrométricas do ar podem acarretar a evaporação das gotas no seu trajeto entre a ponta e o alvo. Neste sentido objetivou-se, com este trabalho, avaliar o efeito das condições psicrométricas do ar e a pressão de trabalho no espectro de gotas da pulverização hidráulica com assistência de ar na barra. O ensaio foi realizado empregando-se um protótipo dotado de um ventilador axial, homogeneizador de fluxo, sensores conjugados de temperatura e umidade relativa, ponta hidráulica e sistema de aquecimento do ar a gás. Com o sistema montado e com o auxílio de um analisador de partículas, avaliou-se a ponta hidráulica JSF 110-02 quanto ao espectro de gotas em quatro diferentes condições psicrométricas do ar (7, 14, 21 e 28 hPa) e em quatro pressões de trabalho (200; 300; 400 e 500 kPa). Ao final, observaram-se perdas por evaporação durante as pulverizações. Para a pressão de trabalho a cada incremento de 1 hPa no valor do déficit de pressão, ocorreu redução do diâmetro das gotas na ordem de 0,0759; 0,518 e 1,514 μm para os parâmetros de DV0,1, DV0,5 e DV0,9, respectivamente. O diâmetro das gotas reduziu com a elevação da pressão de trabalho.
Keywords: Evaporation; Spraying; Pesticides; Evaporação; Pulverização; Agrotóxicos